Effectiveness of Complementary Yoga and Lemon Aromatherapy Therapy on Scores of Burnout Signs and Symptoms in Health Workers in Hospitals - Eko Budi Laksono; Rukmini Syahleman; Wahyono Wahyono; Larantika Hidayati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Schizophrenia is a condition characterized by abnormal social behavior and an inability to understand reality. Mental health Schizophrenia is a severe and serious mental disorder that can become chronic from a young age because it involves changes in physical, psychological and socio-cultural aspects. Inappropriate treatment of schizophrenia patients will always have an impact on anxiety conditions, slurred or confused thinking, decreased auditory hallucinations, reduced social involvement and emotional expression, and lack of motivation. Management is carried out with pharmacological and non-pharmacological complementary, one of which is Burnout is a chronic stress condition related to work and can cause psychological disorders such as low self-esteem, which can ultimately lead to depression and reduce work ability, and affect patient satisfaction with nursing services. One way to overcome burnout is through non-pharmacological therapy, such as yoga and aromatherapy. The purpose of this study was to analyze the application of complementary yoga and aromatherapy to the score of signs and symptoms of burnout in nurses in hospitals. The research method used the Quasi experimental method with two control groups. The population in this study were nurses in hospitals consisting of group 1 (Combination of Yoga Therapy and Lemon Aromatherapy), 2 (Aromatherapy Therapy) and 3 for (Yoga) with 15 pieces each then put into a sealed envelope as many as 45 respondents. The results of the study showed the effect of the combination of yoga and lemon aromatherapy on the score and signs of burnout in nurses in hospitals.